2007
DOI: 10.1021/jo062347b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Borondipyrromethene (BODIPY)-Labeled Sphingosine Derivatives by Cross-metathesis Reaction

Abstract: A new efficient and flexible synthesis of fluorescently labeled sphingosine derivatives from commercially available Garner aldehyde (8) is described. For this, appropriate alkenylated borondipyrromethene (BODIPY) dyes were synthesized and used for the first time in a cross-metathesis reaction, the key step of the approach. The labeled sphingosines with appropriate chain length were accepted as substrates by sphingosine kinases (SPHKs), yielding the corresponding phosphorylated products. One of these derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 17 publications
1
50
0
Order By: Relevance
“…[5,9,10] Opting for a short and easily reproducible route, we used a method which we recently described for efficient synthesis of backbone-labeled sphingolipids. [7,11] Olefin cross metathesis of allyl alocohol 4 [12] and N-Boc-undec-10-enylamine (5) [13] under standard conditions using Grubb's catalyst (2nd generation) gave 6 in excellent yields (Scheme 1) under exclusive formation of the (E)-double bond, as previously observed with similar analogues by us [7,11] and others. [14] The secondary alcohol was protected as tert-butyl-diphenylsilyl (TBDPS) ether prior to cleavage of the acetonide by aqueous acetic acid [15] to afford 7.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…[5,9,10] Opting for a short and easily reproducible route, we used a method which we recently described for efficient synthesis of backbone-labeled sphingolipids. [7,11] Olefin cross metathesis of allyl alocohol 4 [12] and N-Boc-undec-10-enylamine (5) [13] under standard conditions using Grubb's catalyst (2nd generation) gave 6 in excellent yields (Scheme 1) under exclusive formation of the (E)-double bond, as previously observed with similar analogues by us [7,11] and others. [14] The secondary alcohol was protected as tert-butyl-diphenylsilyl (TBDPS) ether prior to cleavage of the acetonide by aqueous acetic acid [15] to afford 7.…”
Section: Resultssupporting
confidence: 58%
“…[6] In this first approach we opted for a chain length of nine C atoms (2, n = 5) between the double bond and the amino group, as previous studies had demonstrated that a C 9 alkyl chain was appropriate to retain biological activity of backbone-functionalized sphingosine analogues to a satisfactory extent. [7] Furthermore it was necessary to introduce a phosphate moiety with appropriate protective groups to provide w-aminosphingosine-1-phosphate 3. Ideally, these protective groups should be UV active and cleavable after immobilization, thus providing a quantitative measure of gel loading.…”
Section: Introductionmentioning
confidence: 99%
“…1C and F , with a max around 550 nm and a shift of the 474 nm peak to 480 nm. However, when similar SphK assays were carried out with the short chain 14-NBD-Sph ( 15 ), no changes in absorption were observed as those seen with 18-NBD-Sph (data not shown).…”
Section: Protein Expression and Purifi Cationmentioning
confidence: 68%
“…BODIPY 540 sphingosine enabled imaging unacylated sphingolipids, which cannot be accomplished with the existing sphingolipid analogs that contain a fl uorescent fatty acid side chain. Furthermore, unlike previously reported fl uorescent sphingosine analogs (7)(8)(9), BODIPY 540 sphingosine can be visualized in parallel with GFP without the use of UV excitation. By exploiting these capabilities, we verifi ed that mammalian cells rapidly internalized BODIPY 540 sphingosine, transported it to the secretory pathway where it was metabolized to more complex fl uorescent sphingolipids, and eventually catabolized these fl uorescent sphingolipids.…”
Section: Discussionmentioning
confidence: 90%